2018
DOI: 10.15548/jt.v25i1.379
|View full text |Cite
|
Sign up to set email alerts
|

Summarising an Explanation Text with a Visual Representation as the Guidelines: How Does this Work to Represent Meaning?

Abstract: Metacognition has been popular in reading area, especially when it is related to comprehension and the representation of meanings. Combining metacognitive strategies to represent meanings from a text has been done by previous scholars to help readers construct meaning. In this paper, we present students" drawings and writings as the results of successive visualisation and summarisation activities in the classroom. We intended to find out the extent to which students" visual representations can be the guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The benefit of doing visualization by the students of this research in the reading process is in line with the previous studies of the same research area from the earliest to the current ones (e.g. Anderson, Kulhavy, 1972); Levin et al, 1973;Levin, 1973;Pressley, 1976;Hobbs, 2001;Woolley, 2010Woolley, , 2007Woolley, , 2006Park, 2012;Kigotho, Fitriani, 2018;Fitriani, Erdiana, Samad, 2019). In addition, the process of achieving comprehension in academic reading as what the students have done in the intervention of this study is suggested to help them in undertaking TOEFL reading section and obtaining an expected score in order to fulfill one of the university's requirements and thereafter to continue further education.…”
Section: Image 4: Nz's Visual Representation Of An Explanation Textsupporting
confidence: 86%
See 1 more Smart Citation
“…The benefit of doing visualization by the students of this research in the reading process is in line with the previous studies of the same research area from the earliest to the current ones (e.g. Anderson, Kulhavy, 1972); Levin et al, 1973;Levin, 1973;Pressley, 1976;Hobbs, 2001;Woolley, 2010Woolley, , 2007Woolley, , 2006Park, 2012;Kigotho, Fitriani, 2018;Fitriani, Erdiana, Samad, 2019). In addition, the process of achieving comprehension in academic reading as what the students have done in the intervention of this study is suggested to help them in undertaking TOEFL reading section and obtaining an expected score in order to fulfill one of the university's requirements and thereafter to continue further education.…”
Section: Image 4: Nz's Visual Representation Of An Explanation Textsupporting
confidence: 86%
“…Generally, among the ways to improve reading comprehension is by using metacognitive strategies. One of well-known strategies in metacognition is visualization (Fitriani, 2015;Fitriani, Erdiana, Samad, 2019;Kigotho, Fitriani, 2018). Studies on visualization have been a topic of investigation in relation to reading comprehension since few decades.…”
Section: Introductionmentioning
confidence: 99%